Evaluation of quality of bread type french by instrumental and sensory methods - Feitosa, Larissa Raphaela Gonçalves de Farias; Maciel, Janeeyre Ferreira; Barreto, Tainá Amaral; Moreira, Ricardo Targino (Semina: Ciências Agrárias, 2013)
The objective of the study was to evaluate the quality of French type bread from bakeries of João Pessoa - PB - Brazil using sensory and instrumental methods. Initially, samples from twelve bakeries selected in this study were submitted for determination of specific volume, moisture, pH, acidity, crust color, crumb color and texture profile, all of these analyses have been performed in triplicate, with 10 repetitions. A sensory acceptance test was applied using a 9-point hedonic scale, with 65 tasters. The samples were evaluated considering attributes of appearance, crust color, crumb color, crust crispness, aroma, taste, texture and the overall acceptability. In instrumental tests, it was observed that most of samples showed moisture below 26% and acidity above 4.5 mL of N/10 NaOH 0.1N/10 g of bread. With respect to the specific volume, satisfactory values were observed in 86,2% of samples (between 5.0 and 8.0 cmÂ³/g), while for skin brightness (60-78) and firmness (2.87 to 6.32 N), this percentage was around 80%. In other textural characteristics was observed that the elasticity varied from 0.91 - 1.93, cohesiveness 0.72 - 0.86 and chewiness of 1.91 - 5.71 N. In relation to sensory acceptance, only 50% of the bakeries have had their bread accepted in all evaluated attributes, with average scores similar or superior to 6. The other samples were rejected due to the lack of crispness, and one of those also had its bread rejected in the attributes of aroma, taste and appearance, therefore showing increased need for adequacy.